Culture. Science. Education: Current Issues - Kuklina A. S., Kuklina I. G., Lesokhina A. M., Shchankina L. N., Gutova S. G., Kholopova A. K., Balan A. V., Pisareva E. V., Shevchenko E. I., Berezkina I. V., Malkanduev I. A., Khanbabaeva O. E., Kvashnin P. R., Makhkamova S. I., Rezak E. V., Sabodina E. P., Melnikov Y. S., Mikhalchenkova N. A., Bolshakov S. N., Bolshakova I. M., Kulikova N. V., Krasilnikova S. V., Arshinik S. P., Lysenko V. V., Kostenko E. G. (Culture. Science. Education: Current Issues, 2020)
the article is devoted to the consideration of features of anaesthetic manual in obese patients. The author outlines that the number of obese people has more than tripled worldwide. The author points out the increasing trend in the incidence of obesity in the Russian Federation in 2020. The purpose of the research is to analyze the data available in the literature on the impact of obesity on the anaesthetic manual and, as a result, the probability of complications in the peri-operative period a as well as the success of surgical interference.
Keywords: масса тела; морбидное ожирение; предоперационная подготовка; анестезия; бариатрическая хирургия; мультимодальная анестезия; body weight; morbid obesity; preoperative preparation; anesthesia; bariatric surgery; multimodal anesthesia